2015
DOI: 10.1088/0004-6256/150/1/5
|View full text |Cite
|
Sign up to set email alerts
|

Prompt Emission by Oh in Comet Hyakutake

Abstract: Laboratory studies predict that the photo-dissociation of H 2 O by solar Ly a photons in the comae of comets should lead to a small percentage of OH in high rotational states of the A 2 S + electronic state. These states should promptly emit a near-ultraviolet (near-UV) photon in a transition to the X 2 P state. From there, the radicals decay to the lowest rotational states by direct rotational transitions and via ro-vibrational cascade in the 1-0 vibrational band, all within the X 2 P state. Normally in Earth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…We also compute abundance ratios, water production rates, the effective active area on the surface of the nucleus required to produce the water based on a standard vaporization model, and the active fraction based on the surface area of the nucleus. For the dust, the fluxes and the now standard proxy for dust production, Afρ, (A'Hearn et al 1984b) are determined from the continuum measurements (see Tables 4,5 and 6). Because of the wide range of solar phase angles, particularly in 1984/85, phase adjustments were made to yield A(0°)fρ.…”
Section: Gas and Dust Production Ratesmentioning
confidence: 99%
“…We also compute abundance ratios, water production rates, the effective active area on the surface of the nucleus required to produce the water based on a standard vaporization model, and the active fraction based on the surface area of the nucleus. For the dust, the fluxes and the now standard proxy for dust production, Afρ, (A'Hearn et al 1984b) are determined from the continuum measurements (see Tables 4,5 and 6). Because of the wide range of solar phase angles, particularly in 1984/85, phase adjustments were made to yield A(0°)fρ.…”
Section: Gas and Dust Production Ratesmentioning
confidence: 99%
“…Since all comets were observed in activity and all had an apparently extended coma, we could determine the Af ρ quantity and its slope (A'Hearn at al. 1984).…”
Section: Observationsmentioning
confidence: 99%
“…It is not yet clear to what extent these new insights will matter for remote sensing observations of comets [32]. Certainly prompt emission has been observed for decades in the [O I] red and green lines at large distances from the nucleus by numerous investigators up to the present [33] and prompt emission in OH has similarly been observed, albeit much less extensively, up to 1000 km from the nucleus both in the near IR [34,35] and in the near UV [36,37]. It is therefore clear that the broader issues raised by the inner-coma observations from Rosetta need to be explored for their implications for remote sensing because 1000 km resolution is common in spectroscopy of comets.…”
Section: (Ii) Comamentioning
confidence: 99%